The effect of pertussis vaccination during pregnancy on the binding epitopes and avidity of anti-pertussis toxin IgG antibodies in infants and their mothers - Knuutila, Aapo; Ivaska, Lauri; Barkoff, Alex-Mikael; van Gageldonk, Pieter; Buisman, Annemarie; Mertsola, Jussi; He, Qiushui (Oxford University Press (OUP), 2026)
Background
Immunization during pregnancy (IP) against pertussis protects young infants, but the maternally derived antibodies blunt the quantity of infants’ antibody responses to their primary vaccination. While the blunting effect has been well studied for antibody quantity, potential blunting that would affect functional characteristics of these antibodies is less studied. This study evaluated the effect of IP on the epitopes and avidity of anti-pertussis toxin (PT) IgG antibodies in infants and their mothers.
Methods
In this prospective open-label controlled clinical trial, 47 pregnant women received diphtheria-tetanus-acellular pertussis (DTaP) vaccine booster, and 22 pregnant women who were not vaccinated served as controls. Sixty-nine infants received hexavalent DTaP vaccine at three and five months of age. Anti-PT IgG antibodies’ binding strength and their ability to inhibit epitope-specific binding of mouse monoclonal antibodies were measured with ELISA in both maternal and infant samples.
Results
In both study groups antibodies in cord blood showed higher epitope-specific inhibition and avidity than what was induced in infants after two primary vaccine doses, at six months. Higher anti-PT IgG concentrations (p<0.001) and epitope-specific inhibition targeting 1B7 (p=0.049) and 11E6 (p=0.024) were noted at six months in control group infants, suggesting epitope-specific blunting in IP group. No difference was observed in the avidity of anti-PT IgG at six months between two study groups. The increase in avidity after vaccination was the highest in those mothers and infants with lower baseline avidity.
Conclusions
Immunization during pregnancy decreased primary vaccination-induced antibody responses disproportionately against different PT epitopes in infants.
The trial was registered in the EU Clinical Trial database (EudraCT number 2019-001986-34, https://www.clinicaltrialsregister.eu)